PEMBELAJARAN DARI BIOGRAFI I PUTU GEDE SUWITHA: POLITIKUS MENJADI GURU BESAR UNIVERSITAS UDAYANA - Fadila, Anisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study delves into the insights garnered from the biography of I Putu Gede Suwitha, a History Professor at Udayana University. The biography unfolds the remarkable journey of I Putu Gede Suwitha, showcasing his unwavering commitment to academia, accentuating significant teaching contributions, and highlighting the importance of family values. Despite being born in 1995, I Putu Gede Suwitha encountered administrative challenges, resulting in a birth year discrepancy on official documents. Raised by civil servant parents, he exhibited early intellectual curiosity, foreshadowing his eventual role as a Professor. The research questions will be addressed through interviews with the main character and those closest to him, employing the methodologies of cultural history and Bourdieu's theory. Within this framework, it was discovered that his journey to becoming a professor was fueled by the desire to enhance the education of Udayana History students. In conclusion, I Putu Gede Suwitha faced numerous challenges on his academic path to professorship. The implication of I Putu Gede Suwitha holding a position as a professor at Udayana University is evident in the establishment of the History of Thought course.